Apoptosis and necrosis in the circumventricular organs after experimental subarachnoid hemorrhage as detected with annexin V and caspase 3 immunostaining. (December 2014) - Edebali, Nurullah; Tekin, İshak Özel and Açıkgöz, Bektaş and Açıkgöz, Şerefden and Barut, Figen and Sevinç, Nergis and Sümbüloğlu, Vildan
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives : The circumventricular organs (CVOs) are essential for most autonomic and endocrine functions. Trauma and bleeding can affect their function. The aim of this study was to investigate apoptosis and necrosis in CVOs in the early period after experimental subarachnoid hemorrhage (SAH) in rats, using annexin V affinity and caspase 3 immunostaining. Methods : Three experimental groups were used: Days 1 and 2 after SAH, and a control group, seven Wistar albino rats each. Subarachnoid hemorrhage was accomplished by transclival basilar artery puncture. Rats were perfused with 0·9% NaCl and 0·1M phosphate buffer pH 7·4 until heart stoppage. Apoptosis and necrosis in CVOs were measured by flow cytometry with annexin V staining, and by caspase 3 immunostaining. Results : Apoptosis in the organum vasculosum lamina terminalis (OVLT), median eminence (ME), and area postrema (AP) was significantly higher in the Day 1 group than in the control group. Apoptosis in the subfornicial organ (SFO), OVLT, ME, and AP was significantly higher in the Day 2 group than in the control group. There were significant differences between the Day 1 and Day 2 groups, except for AP. Necrosis in SFO and OVLT was significantly higher in the Day 2 group than in the Day 1 or control groups, whereas necrosis in the ME and AP did not differ between the three groups. Caspase 3-positive cell density was more intense in the Day 2 group than in the Day 1 and control groups. Discussion : Prevention of apoptosis may potentially improve impaired functions of CVOs after SAH.